2021
DOI: 10.1111/nhs.12831
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses' strategies when speaking up for patient safety: A qualitative study

Abstract: The purpose of this study was to understand student nurses' perceptions and experiences of witnessing and responding to risks to patient safety during their integrated learning experiences. This qualitative study's two‐phased approach included individual semi‐structured interviews, followed by focus group discussions with students. Participants included 53 pre‐registration nursing students recruited from the first, second, and third years of study at two Australian universities. All had attended at least one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Students value the fact that their role as students prevents them from expressing themselves openly. 40 The findings are consistent with the review by Albert et al which showed that students wanted ethical care, but lacked the ability to decide for themselves, and were torn between silence and denunciation. 41 In their reflections, the students acknowledge their inaction, and intention to improve in the future.…”
Section: Performance Evaluation Of Other Professionalssupporting
confidence: 88%
“…Students value the fact that their role as students prevents them from expressing themselves openly. 40 The findings are consistent with the review by Albert et al which showed that students wanted ethical care, but lacked the ability to decide for themselves, and were torn between silence and denunciation. 41 In their reflections, the students acknowledge their inaction, and intention to improve in the future.…”
Section: Performance Evaluation Of Other Professionalssupporting
confidence: 88%
“…Due to this, the FM staff should also work with the greatest interest of the patients at heart and make sure that their operating hours and services provided does not adversely impact on the administrative process to continually ensure quality patients health-care experience. This means having a health-care setting where both health-care professionals (both core and supporting) and patients can have their say concerning safety issues that concerns them without fear of culpability or reprisal (Fagan et al , 2021; Lee et al , 2021). It implies encouraging an environment where both health-care professionals and patients would be free to report risks and well-being occurrences with the aim of learning from them and lessening their repetition (Fancourt and Finn, 2019; WHO, 2016b).…”
Section: Review Of Findings and Their Implicationsmentioning
confidence: 99%
“…Higher persistence and personal goals were factors identified in qualitative studies. In the study byFagan et al (2021), students reported that they were afraid to talk about patient safety in a clinical setting and needed more time to decide whether to talk about patient safety issues or not. The second study (Lundell Rudberg et al, 2022) described how it is necessary to set personal goals to be able to proceed in accordance with safe practices and not always follow mentors who sometimes do not follow safe practices.…”
mentioning
confidence: 99%